Maybe someday : a novel - Hoover, Colleen (New York : Atria Books, 2014)
When she discovers that her boyfriend is cheating on her, Sydney, a 22-year-old college student, must decide what to do next, especially when she becomes captivated by her mysterious neighbor Ridge
When she discovers that her boyfriend is cheating on her, Sydney, a college student, must decide what to do next. She becomes captivated by her mysterious neighbor Ridge, and can't stop listening to the passionate way he plays his guitar every evening out on his balcony. They soon find themselves needing each other in more ways than one.
Keywords: College students -- Fiction; Friendship -- Fiction; Betrayal -- Fiction; Man-woman relationships -- Fiction; Guitarists -- Fiction; Betrayal; College students; Friendship; Guitarists; Man-woman relationships; Romance fiction; Fiction; Romance fiction; Love stories